Alternative Approach for Occipital Headache Surgery: The Use of a Transverse Incision and "W" Flaps. Issue 4 (April 2019) - Afifi, Ahmed M.; Carbullido, Mary K.; Israel, Jacqueline S.; Sanchez, Ruston J.; Albano, Nicholas J.
Abstract : Summary: The most commonly used approach for a greater occipital nerve decompression is through a vertical midline incision, with multiple authors reporting favorable long-term outcomes. A transverse approach to the occipital nerves has been described, yet it does not include the use of fat flaps to insulate the decompressed nerves. In this study, we describe the use of a single transverse incision with modified "W" fat flaps to decompress both the greater and lesser occipital nerves. This allows for wider exposure of the nerves without the need for an additional incision to access the lesser occipital nerve. The described technique provides increased reach and versatility of the fat flap, allowing for coverage over a longer course of the nerve and further cephalad, close to the bony skull base. In addition, the fat flaps cover the greater occipital nerve closer to its native position, as opposed to bringing the nerve into a subcutaneous position. This, theoretically, keeps the nerve in a more protected deep position and technically makes it easier to avoid any tendency for kinking the nerves while wrapping them with the fat flap. Our experience has demonstrated that this modified technique is not only safe but also efficacious in affecting a statistically significant reduction (70% improvement, P = 0.004) in migraine headache index and HIT-6 scores. This study provides further evidence that nerve decompression for headache following the principles described by Guyuron is an efficacious and reproducible procedure and that a proper nerve decompression is effective in reducing headache.